Erythemal irradiance at the Magellan´s region and Antarctic ozone hole 1999-2005 - C. Casiccia (Atmósfera, 2008)
The most austral...Antarctic Ozone Hole (AOH), occasionally receives enhanced levels of ultraviolet B radiation (UV-B: 280-320nm). Ultraviolet erythemal irradiance measurements began in 1999 by the University of Magallanes in PuntaArenas (Lat. 53.0° S; Lon. 70.9° W), Chile, with the installation of four instruments in different locations inthe Magallanes region, which is the southernmost region in Chile and the nearest to the Antarctic Continent. Data from Solar Light instruments, the Brewer spectrophotometer (Serial 180) and the Total Ozone MappingSpectrometer (TOMS) from 1999 to 2005 for the Magellan´s Region is presented in this paper. These data...ozone column at these latitudes is still uncertain. Data of erythemal measurements from the stations that arepart of the Magallanes network were analyzed, with extra attention given to the spring-summer period whenthe activity of the AOH is more intense. On several occasions important decreases down to 20-53% in thetotal ozone column were observed. Along with these decreases, increased levels of UV-B radiation wereobserved. When compared to normal daily concentration values of the total ozone, the days with increasedUV-B levels reached values between ~50 and ~200% above normal at the different stations